Identification and physiological characterization of thermo-tolerant rice genotypes - ZHOU Wei-hui; XUE Da-wei; ZHANG Guo-ping (浙江大学学报. 农业与生命科学版, 2012)
The experiments were conducted to identify thermo-tolerant rice genotypes and characterize physiological traits relevant to heat stress tolerance. Seventy-two rice genotypes were exposed to high temperature (40℃ /35 ℃, 14 h/10 h) for 12 d at heading stage, and floret fertility was examined. The similar results were obtained in the two years experiments that there was a distinctly genotypic difference in floret fertility as affected by heat stress. When rice seedlings were exposed to heat stress, chlorophyll content (SPAD value), plant height, root length, shoot and root biomass were dramatically reduced, with thermo-tolerant genotypes being relatively less affected than sensitive ones. Meanwhile, high temperature enhanced membrane lipid peroxidation, as expressed by malondialdehyde content and increased superoxide dismutase (SOD) activity. Thermo-tolerant genotypes had less and more increase in MDA content and SOD activity than sensitive ones under heat stress relative to the control, respectively. Accordingly the thermo-tolerant genotypes were identified, with genotypes CJ6, MY46 and JX17 being highly thermo-tolerant, MH63, Kasalath and IRAT4217 being very sensitive.